2017
DOI: 10.3390/mi9010003
|View full text |Cite
|
Sign up to set email alerts
|

Rhombic-Shaped Channel Stent with Enhanced Drug Capacity and Fatigue Life

Abstract: A drug-eluting stent with rhombic-shaped drug reservoirs is proposed, aimed at providing long-term drug delivery and enhanced fatigue life. Unique rhombic-shaped reservoirs or channels on the stent struts can increase the total drug capacity and improve the stress distribution for longer fatigue life, without compromising other important clinical attributes. Our rhombic-shaped channel stent increases the total drug capacity by multiple times. Its fatigue safety factor, even with the large rhombic cutouts on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Several finite element models were developed to evaluate the structural integrity and pulsatile fatigue life of a hybrid flow diverter subjected to loading conditions consistent with current manufacturing and clinical practice [16][17]. These included hybrid flow diverter expansion and its corresponding heat treatment during manufacturing, crimping of the hybrid flow diverter inside a catheter for delivery, its release into a blood vessel, and pulsatile fatigue life under systolic/diastolic cycles relative to heart beats.…”
Section: Manufacturing Simulationmentioning
confidence: 99%
“…Several finite element models were developed to evaluate the structural integrity and pulsatile fatigue life of a hybrid flow diverter subjected to loading conditions consistent with current manufacturing and clinical practice [16][17]. These included hybrid flow diverter expansion and its corresponding heat treatment during manufacturing, crimping of the hybrid flow diverter inside a catheter for delivery, its release into a blood vessel, and pulsatile fatigue life under systolic/diastolic cycles relative to heart beats.…”
Section: Manufacturing Simulationmentioning
confidence: 99%
“…Observational studies have shown promising results in the use of drug-eluting stents for ISR lesions [ 105 , 106 ]. A drug-eluting stent is a bare-metal stent with a drug coating [ 107 ] that minimizes neointimal hyperplasia and lessens repeat revascularization in BMS use. DES was developed through the application of different types and combinations of drugs as well as design materials and structural schemes.…”
Section: In-stent Restenosis Treatmentmentioning
confidence: 99%
“…DES design also has a key function in preventing neointima proliferation. No surface coating is required when a channel or depot stent (reservoir) is used, which may be loaded with a single, or else multiple, drugs for programmed delivery [ 107 , 130 , 131 ].…”
Section: In-stent Restenosis Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulated Von-Mises stress distributions of the multi-connector and single-connector stents are shown in Figure 8. In general, coronary stents use ductile materials that can achieve large deformation during balloon expansion [34]. They obey the Von-Mises stress criterion, expressed as σvonmises=false[(σ1σ2)2+(σ2σ3)2+(σ3σ1)2false]122σy where σ1, σ2, and σ3 are principle stresses.…”
Section: Simulationsmentioning
confidence: 99%